#TITLE_ALTERNATIVE# - KURNIAWAN NIM : 30715008 , FRANSISKA
Cancer is a disease related to the abnormal growth of cell. The potency of porphyrin compounds as anticancer agents have already known due to their affinity to the DNA, however, the study about their interaction with the non-DNA target is still limited. The purpose of present research was to obtain porphyrin derivatives as a candidate of anticancer and information about their interaction to the non- DNA target. Five known porphyrin derivatives and three novel porphyrin derivatives bearing bis(3,4-ethylcarboxymethylenoxy) phenyl (BECP) as mesosubstituent were used to study their interaction with their targets (in silico study), synthesized, and tested their cytotoxicity activity against cancer cell line. Three novel porphyrins with meso-susbituent of BECP were designed as candidates of radiopharmaceutical ligand and their interactions with the targets after being labeled with rhenium (Re) and technetium (Tc) were studied by in silico. The interactions of porphyrin derivatives with protein target of cancer such as spleen tyrosin kinase, epidermal growth factor receptor, carbonic anhydrase IX (CAIX), and REV-ERBβwere then analyzed after performing molecular docking with AutoDock 4.2 and molecular dynamic simulation with Gromacs2016. The simulations showed that studied porphyrins have affinity to the targets and the interactions were dominated by hydrophobic interactions. Re- and Tc-porphyrin also have affinity to the targets although the porphyrins have been already labeled. For each protein target, the porphyrin with best affinity was determined and the free binding energy between the best porphyrin-target complex was also calculated by MM/PBSA method. The toxicity of all porphyrins were also predicted by using ADMET Predictor v 8.1. In general, it was predicted that porphyrin derivatives are cardiotoxic, hepatotoxic, and toxic to reproduction system, however, they are not mutagenic, and their carcinogenicity level were not high. All porphyrin derivatives were successfully synthesized by Adler method, and they were characterized by UV/Vis, 1 H-NMR, 13 C-NMR, and LRMS MALDI-TOF. The reaction pathway in this Adler method was also studied by in silico study and it was known that the keystep of the reaction is the first step when the aldehyde reacts with pyrrole based on the reactivity of the aldehyde. The cytotoxicity activities of all porphyrin derivatives were tested by MTT assay against cancer cell (HeLa, WIDR, MCF-7, T47D, and HepG2 cell lines) and normal cell (Vero cell line). The in vitro test results showed iv that all studied porphyrins have good affinity against cancer cell, having higher affinity to the cancer cell than to that of the normal cell, and they are categorized as marginally active compound with the IC50 < 5 mM. Based on these results, it can be concluded that all studied porphyrins were potential as an anticancer agents, and porphyrins bearing bis(3,4-ethylcarboxymethylenoxy) phenyl (BECP) as mesosubstituent have better potential as a radiopharmaceutical ligand kit after the ester groups of BECP were hydrolyzed.